VARIASI KADAR SUKROSA SEBAGAI BAHAN PEMANIS DALAM FORMULASI NUTRASEUTIKAL SEDIAAN GUMMY CANDIES SARI BUAH MARKISA KUNING (Passiflora edulis var. flavicarpa) - Feris Firdaus; Vicky Agung Kresnanto; Fajriyanto Fajriyanto (Teknoin, 2014)
Passion fruit (Passiflora edulis) is one kind of plant that is commonly grown by our society. In the yellow passion fruit (Passiflora edulis var. Flavicarpa) contained vitamin C and vitamin A which is very high. The usage of passion fruit juice as nutraceuticals products that are rich in vitamins C and A is still relatively rare. Demands of people who want to get an interesting kind of preparation and easy to use push of this study which aims to produce gummy candies. Gummy candies preparations were made using a base of corn syrup, a sweetener mannitol with sucrose content variation of 4.49%, 8.98%, 13.47%, 17.96% and 22.45%. Manufacture of yellow passion fruit juice using freeze drying method is performed on the resulting fruit juice. Organoleptic test was conducted after the yellow passion fruit juice formed. Testing the physical properties of the preparations which have become gummy candies include organoleptic testing, weights uniformity test and the level of preference test (hedonict test) by the respondents to the color, taste, smell and shape, then the results were compared with the requirements in the literature and the results of statistical analysis using one way anova. Formula 3 that was containing sucrose 13.47% is the best formula compared with other formula, a coefficient of variation for weight uniformity test was 2.91%. While for organoleptic test and hedonict test for the color, flavor, smell and shape of the formula 4 by respondents indicated that the sucrose content of 17.96% has the best look and feel to become the most preferred formula by respondents.